Pregunta
upstudy study bank question image url

> \( x^{2}-5 x+6=0 \) \( >x^{2}-7 x=9 \) \( >2(x+1)^{2}-5=0 \) \( >(2 x-1)(x+3)=2 \) \( >7 x^{2}=2-7 x \) \( >3 x-2 x(x+1)=2 \) NOTE CHECK SOLVE THE FOLLOWING THROUGH COMPLETING THE SQUARE

Ask by Wells Bowen. in South Africa
Feb 21,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

Here are the solutions for each equation using completing the square: 1. \( x^{2}-5 x+6=0 \): \( x=2 \) or \( x=3 \) 2. \( x^{2}-7 x=9 \): \( x=\frac{7-\sqrt{85}}{2} \) or \( x=\frac{7+\sqrt{85}}{2} \) 3. \( 2(x+1)^{2}-5=0 \): \( x=-\frac{2+\sqrt{10}}{2} \) or \( x=\frac{-2+\sqrt{10}}{2} \) 4. \( (2 x-1)(x+3)=2 \): \( x=-\frac{5+\sqrt{65}}{4} \) or \( x=\frac{-5+\sqrt{65}}{4} \) 5. \( 7 x^{2}=2-7 x \): \( x=-\frac{7+\sqrt{105}}{14} \) or \( x=\frac{-7+\sqrt{105}}{14} \) 6. \( 3 x-2 x(x+1)=2 \): No real solution

Solución

Solve the quadratic equation by following steps: - step0: Solve by factoring: \(x^{2}-5x+6=0\) - step1: Factor the expression: \(\left(x-3\right)\left(x-2\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-3=0\\&x-2=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=3\\&x=2\end{align}\) - step4: Rewrite: \(x_{1}=2,x_{2}=3\) Solve the equation \( 3 x-2 x(x+1)=2 \). Solve the equation(The complex numbers system) by following steps: - step0: Solve using the quadratic formula in the complex numbers system: \(3x-2x\left(x+1\right)=2\) - step1: Expand the expression: \(x-2x^{2}=2\) - step2: Move the expression to the left side: \(x-2x^{2}-2=0\) - step3: Rewrite in standard form: \(-2x^{2}+x-2=0\) - step4: Multiply both sides: \(2x^{2}-x+2=0\) - step5: Solve using the quadratic formula: \(x=\frac{1\pm \sqrt{\left(-1\right)^{2}-4\times 2\times 2}}{2\times 2}\) - step6: Simplify the expression: \(x=\frac{1\pm \sqrt{\left(-1\right)^{2}-4\times 2\times 2}}{4}\) - step7: Simplify the expression: \(x=\frac{1\pm \sqrt{-15}}{4}\) - step8: Simplify the expression: \(x=\frac{1\pm \sqrt{15}\times i}{4}\) - step9: Separate into possible cases: \(\begin{align}&x=\frac{1+\sqrt{15}\times i}{4}\\&x=\frac{1-\sqrt{15}\times i}{4}\end{align}\) - step10: Simplify the expression: \(\begin{align}&x=\frac{1}{4}+\frac{\sqrt{15}}{4}i\\&x=\frac{1-\sqrt{15}\times i}{4}\end{align}\) - step11: Simplify the expression: \(\begin{align}&x=\frac{1}{4}+\frac{\sqrt{15}}{4}i\\&x=\frac{1}{4}-\frac{\sqrt{15}}{4}i\end{align}\) - step12: Rewrite: \(x_{1}=\frac{1}{4}-\frac{\sqrt{15}}{4}i,x_{2}=\frac{1}{4}+\frac{\sqrt{15}}{4}i\) - step13: Remove the complex number(s): \(\textrm{No real solution}\) Solve the equation \( 2(x+1)^{2}-5=0 \). Solve the quadratic equation by following steps: - step0: Solve using the quadratic formula: \(2\left(x+1\right)^{2}-5=0\) - step1: Expand the expression: \(2x^{2}+4x-3=0\) - step2: Solve using the quadratic formula: \(x=\frac{-4\pm \sqrt{4^{2}-4\times 2\left(-3\right)}}{2\times 2}\) - step3: Simplify the expression: \(x=\frac{-4\pm \sqrt{4^{2}-4\times 2\left(-3\right)}}{4}\) - step4: Simplify the expression: \(x=\frac{-4\pm \sqrt{40}}{4}\) - step5: Simplify the expression: \(x=\frac{-4\pm 2\sqrt{10}}{4}\) - step6: Separate into possible cases: \(\begin{align}&x=\frac{-4+2\sqrt{10}}{4}\\&x=\frac{-4-2\sqrt{10}}{4}\end{align}\) - step7: Simplify the expression: \(\begin{align}&x=\frac{-2+\sqrt{10}}{2}\\&x=\frac{-4-2\sqrt{10}}{4}\end{align}\) - step8: Simplify the expression: \(\begin{align}&x=\frac{-2+\sqrt{10}}{2}\\&x=-\frac{2+\sqrt{10}}{2}\end{align}\) - step9: Rewrite: \(x_{1}=-\frac{2+\sqrt{10}}{2},x_{2}=\frac{-2+\sqrt{10}}{2}\) Solve the equation \( x^{2}-7 x=9 \). Solve the quadratic equation by following steps: - step0: Solve using the quadratic formula: \(x^{2}-7x=9\) - step1: Move the expression to the left side: \(x^{2}-7x-9=0\) - step2: Solve using the quadratic formula: \(x=\frac{7\pm \sqrt{\left(-7\right)^{2}-4\left(-9\right)}}{2}\) - step3: Simplify the expression: \(x=\frac{7\pm \sqrt{85}}{2}\) - step4: Separate into possible cases: \(\begin{align}&x=\frac{7+\sqrt{85}}{2}\\&x=\frac{7-\sqrt{85}}{2}\end{align}\) - step5: Rewrite: \(x_{1}=\frac{7-\sqrt{85}}{2},x_{2}=\frac{7+\sqrt{85}}{2}\) Solve the equation \( (2 x-1)(x+3)=2 \). Solve the quadratic equation by following steps: - step0: Solve using the quadratic formula: \(\left(2x-1\right)\left(x+3\right)=2\) - step1: Expand the expression: \(2x^{2}+5x-3=2\) - step2: Move the expression to the left side: \(2x^{2}+5x-5=0\) - step3: Solve using the quadratic formula: \(x=\frac{-5\pm \sqrt{5^{2}-4\times 2\left(-5\right)}}{2\times 2}\) - step4: Simplify the expression: \(x=\frac{-5\pm \sqrt{5^{2}-4\times 2\left(-5\right)}}{4}\) - step5: Simplify the expression: \(x=\frac{-5\pm \sqrt{65}}{4}\) - step6: Separate into possible cases: \(\begin{align}&x=\frac{-5+\sqrt{65}}{4}\\&x=\frac{-5-\sqrt{65}}{4}\end{align}\) - step7: Rewrite the fraction: \(\begin{align}&x=\frac{-5+\sqrt{65}}{4}\\&x=-\frac{5+\sqrt{65}}{4}\end{align}\) - step8: Rewrite: \(x_{1}=-\frac{5+\sqrt{65}}{4},x_{2}=\frac{-5+\sqrt{65}}{4}\) Solve the equation \( 7 x^{2}=2-7 x \). Solve the quadratic equation by following steps: - step0: Solve using the quadratic formula: \(7x^{2}=2-7x\) - step1: Move the expression to the left side: \(7x^{2}-2+7x=0\) - step2: Rewrite in standard form: \(7x^{2}+7x-2=0\) - step3: Solve using the quadratic formula: \(x=\frac{-7\pm \sqrt{7^{2}-4\times 7\left(-2\right)}}{2\times 7}\) - step4: Simplify the expression: \(x=\frac{-7\pm \sqrt{7^{2}-4\times 7\left(-2\right)}}{14}\) - step5: Simplify the expression: \(x=\frac{-7\pm \sqrt{105}}{14}\) - step6: Separate into possible cases: \(\begin{align}&x=\frac{-7+\sqrt{105}}{14}\\&x=\frac{-7-\sqrt{105}}{14}\end{align}\) - step7: Rewrite the fraction: \(\begin{align}&x=\frac{-7+\sqrt{105}}{14}\\&x=-\frac{7+\sqrt{105}}{14}\end{align}\) - step8: Rewrite: \(x_{1}=-\frac{7+\sqrt{105}}{14},x_{2}=\frac{-7+\sqrt{105}}{14}\) Here are the solutions for each equation using the method of completing the square: 1. **Equation:** \( x^{2}-5 x+6=0 \) - Completing the square gives us: \[ (x-2)(x-3)=0 \] - **Solutions:** \( x_{1}=2, x_{2}=3 \) 2. **Equation:** \( x^{2}-7 x=9 \) - Rearranging gives us: \[ x^{2}-7 x - 9=0 \] - Completing the square results in: \[ x = \frac{7 \pm \sqrt{85}}{2} \] - **Solutions:** \( x_{1}=\frac{7-\sqrt{85}}{2}, x_{2}=\frac{7+\sqrt{85}}{2} \) 3. **Equation:** \( 2(x+1)^{2}-5=0 \) - Rearranging gives us: \[ 2(x+1)^{2}=5 \] - Completing the square results in: \[ x = -1 \pm \frac{\sqrt{10}}{2} \] - **Solutions:** \( x_{1}=-\frac{2+\sqrt{10}}{2}, x_{2}=\frac{-2+\sqrt{10}}{2} \) 4. **Equation:** \( (2 x-1)(x+3)=2 \) - Rearranging gives us: \[ 2x^2 + 5x - 5 = 0 \] - Completing the square results in: \[ x = \frac{-5 \pm \sqrt{65}}{4} \] - **Solutions:** \( x_{1}=-\frac{5+\sqrt{65}}{4}, x_{2}=\frac{-5+\sqrt{65}}{4} \) 5. **Equation:** \( 7 x^{2}=2-7 x \) - Rearranging gives us: \[ 7x^2 + 7x - 2 = 0 \] - Completing the square results in: \[ x = \frac{-7 \pm \sqrt{105}}{14} \] - **Solutions:** \( x_{1}=-\frac{7+\sqrt{105}}{14}, x_{2}=\frac{-7+\sqrt{105}}{14} \) 6. **Equation:** \( 3 x-2 x(x+1)=2 \) - Rearranging gives us: \[ -2x^2 + x - 2 = 0 \] - Completing the square shows that there are no real solutions. - **Solutions:** No real solution These solutions provide the values of \( x \) for each equation as required.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To tackle these equations using the completing the square method, let's transform the quadratic equations into perfect square forms systematically! First up, for the equation \(x^{2} - 5x + 6 = 0\), we can rewrite it as \(x^{2} - 5x = -6\). Now, take half of the coefficient of \(x\) (which is -5), square it (giving \(\frac{25}{4}\)), and add it to both sides: \[x^{2} - 5x + \frac{25}{4} = -6 + \frac{25}{4} \Rightarrow \left(x - \frac{5}{2}\right)^{2} = \frac{1}{4} \] which leads to \(x - \frac{5}{2} = \pm \frac{1}{2}\), resulting in \(x = 3\) or \(x = 2\). Next, for \(2(x + 1)^{2} - 5 = 0\), we first rearrange it: \[2(x + 1)^{2} = 5 \Rightarrow (x + 1)^{2} = \frac{5}{2}\] Now, taking the square root gives us \(x + 1 = \pm \sqrt{\frac{5}{2}}\) then subtracting 1 leads to solutions \(x = -1 + \sqrt{\frac{5}{2}}\) and \(x = -1 - \sqrt{\frac{5}{2}}\). Completing the square not only helps find roots efficiently but also provides insights into the graph of the function, illustrating its minimum points or intercepts! To up your math game, check out the classic "Algebra and Trigonometry" by Blitzer. It offers a clear step-by-step approach to concepts like completing the square along with a variety of practice problems! Another gem is "The Art of Problem Solving" series – it’s packed with engaging challenges that make solving quadratics so much more fun!

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad